2020
DOI: 10.15694/mep.2020.000243.1
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips on how to motivate healthcare professions students and their supervisors for Interprofessional Education

Abstract: Special efforts in rotations are necessary to have students from different professions learn with, from and about each other to improve their collaboration and the quality of care. The twelve tips derived from the lived experiences and research from the authors, are intended to stimulate motivation for interprofessional education in students and their supervisors. Internalization of the value students place on interprofessional learning will improve their readiness for future interprofessional collaboration. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…It means that if work motivation is increased by one unit, it will impact patient safety. These results align with previous research (Dongen et al, 2016;Nygren et al, 2021;Visser et al, 2020;Yune et al, 2020); work motivation can improve patient safety.…”
Section: The Effect Of Work Motivation On Patient Safetysupporting
confidence: 92%
See 3 more Smart Citations
“…It means that if work motivation is increased by one unit, it will impact patient safety. These results align with previous research (Dongen et al, 2016;Nygren et al, 2021;Visser et al, 2020;Yune et al, 2020); work motivation can improve patient safety.…”
Section: The Effect Of Work Motivation On Patient Safetysupporting
confidence: 92%
“…It means that if one unit increases interprofessional collaboration, it will impact work motivation by 0.786. These results align with previous research (Dongen et al, 2016;Nygren et al, 2021;Visser et al, 2020;Yune et al, 2020) that interprofessional collaboration can significantly increase work motivation.…”
Section: The Effect Of Interprofessional Collaboration On Work Motiva...supporting
confidence: 92%
See 2 more Smart Citations
“…Research has indeed found that in pursuit of establishing professional identity and championing their chosen profession, the importance of collaborative practice may be overlooked by healthcare students (World Health Organization, 2013). According to the self-determination theory, an individual's motivation to engage in a task is rooted in the perceived value as well as the principles of autonomy, competence and relatedness (Visser et al, 2020). We therefore propose that universities must underscore the value of IPCP to healthcare students, Additionally, seeking feedback from their peers regarding clinical decisions adequately fulfils the principle of competence (Visser et al, 2020).…”
Section: Modifying Healthcare Student Curricula To Facilitate Interpr...mentioning
confidence: 99%